ANATOMY APPLICATION FOR SPECIAL NEEDS CHILDREN IN THEMATIC LEARNING - KARIMAH, VIA HAIYUN; SULEMAN, MUH. ASHARIF; IDAYANTI, ZULFI; SUHARDI, MUHAMAD (EDUKIDS : Jurnal Inovasi Pendidikan Anak Usia Dini, 2024)
Education is something for everyone, including children with special needs as regulated in Law no. 20 of 2003 Article 8 paragraph 1. The challenge of education for children with special needs is the cognitive aspect and adapting learning to suit their abilities and needs. The aim of this research is to find out how the anatomy application is implemented and to analyze how much influence this application has on students with special needs in thematic learning in theme 3 subtheme 1. The research method used is mixed methods quantitative qualitative. The quantitative data collection technique uses one group pretest-posttest and is then tested for validity, realism and hypothesis using Paired Sample Ttest analysis. Meanwhile, qualitative data collection techniques involve in-depth interviews with homeroom teachers. Participants in the quantitative approach were grade 5 children who had special needs such as slow learners, intellectual disabilities, multiple disabilities, and ADHD at SD TS Yogyakarta. The results of this research indicate that anatomy applications can be implemented with teacher supervision. Children can be divided into groups and access the application in turn. Students' cognitive development and interests vary according to their specific types of needs. Based on the results of quantitative analysis, it is known that the P-value is 0.020. This means that there is a significant difference between the groups before and after using anatomy applications in thematic learning. ABSTRAKPendidikan adalah hak bagi setiap individu, termasuk anak berkebutuhan khusus, sebagaimana diatur dalam Undang-Undang Nomor 20 Tahun 2003 Pasal 8 Ayat 1. Tantangan dalam pendidikan untuk anak berkebutuhan khusus terletak pada aspek kognitif serta penyesuaian pembelajaran yang sesuai dengan kemampuan dan kebutuhan mereka. Penelitian ini bertujuan untuk mengetahui implementasi aplikasi anatomi serta menganalisis pengaruh aplikasi ini terhadap anak berkebutuhan khusus dalam pembelajaran tematik pada tema 3 subtema 1. Metode penelitian yang digunakan adalah metode campuran (mixed methods) kuantitatif-kualitatif. Teknik pengumpulan data kuantitatif menggunakan desain one group pretest-posttest dan kemudian diuji validitas, reliabilitas, serta hipotesis menggunakan analisis Paired Sample T-Test. Sementara itu, teknik pengumpulan data kualitatif dilakukan melalui wawancara mendalam dengan wali kelas. Partisipan pendekatan kuantitatif adalah siswa kelas 5 yang memiliki kebutuhan khusus, seperti lamban belajar, tunagrahita, disabilitas ganda, dan ADHD di SD TS Yogyakarta. Hasil penelitian menunjukkan bahwa aplikasi anatomi dapat diimplementasikan dengan pengawasan guru. Anak-anak dapat dibagi menjadi kelompok dan mengakses aplikasi secara bergiliran. Perkembangan kognitif dan minat siswa bervariasi sesuai dengan jenis kebutuhan khusus mereka. Berdasarkan hasil analisis kuantitatif, diketahui bahwa nilai P adalah 0,020. Hal ini menunjukkan adanya perbedaan signifikan antara kelompok sebelum dan sesudah menggunakan aplikasi anatomi dalam pembelajaran tematik.